Preparation and Characterization of Molecular Complexes of Fenofibrate Cocrystal - Payghan, Dr. Santosh Ambadas (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The objective of this study was to investigate whether the miscibility of a drug and coformer, as predicted by Hansen solubility parameter (HSP), can indicate cocrystal formulation. It was also our aim to evaluate various HSP-based approaches in miscibility predication. HSP for fenofibrate drug over 20 coformers was calculated according to the group contribution method. Materials and Methods: The selection of coformer was based on hydrogen bond present in structure which clearly shows the importance of hydrogen bonding in forming cocrystals. Solubility parameters for solutes are obtained by group contribution method. Result and Discussion: In the present investigation, these methods were employed to arrive at the solubility parameter values. The basic steps in Fedor’s method are to open the rings and treat the resultant structure as an open-chain compound. These were sum-up, and the solubility parameter was calculated as square root of the sum of energy of mixing substituent constants divided by the sum of molar volume substituent constants. Hoy’s procedure expressed in the ratio of molar attraction constant to molar volume. The resultant δ values of drug and coformers are compared, and their solid state miscibility is expressed. Possibility of cocrystal formulation by Krevelen’s is Δδ < 5 MP and Greenhalgh Δδ < 7 MP. The present investigation deals with the formulation of coformer (saccharin, succinic acid, and sucrose) based on cocrystals fenofibrate by different methods and solid-state characterization of prepared cocrystals. Fenofibrate and coformers in molar ratio were used to formulate molecular complexes by solution evaporation, slow evaporation, antisolvent addition, net grinding method, and solvent-drop grinding methods. The prepared molecular complexes were characterized by powder X-ray diffraction, differential scanning calorimetry, Fourier-transform infrared spectroscopy, and in vitro dissolution study. Conclusion: Considerable improvement in the dissolution rate of fenofibrate from optimized cocrystal formulation was due to an increased solubility that is attributed to the supersaturation from the fine cocrystals which is faster due to large specific surface area of small particles and prevention of phase transformation to pure fenofibrate.